Decorin: a possible marker for fetal growth restriction - Caglar, Mete; Yavuzcan, Ali; Goksu, Mehmet; Bulbul, Gul Alkan; Isenlik, Bekir Sitki; Ustun, Yusuf; Kumru, Selahattin (Taylor & Francis Ltd, 2014)
The aim of this study was to compare decorin (DCN) levels between pregnancies complicated by idiopathic fetal growth restriction (FGR) and uncomplicated pregnancies and to determine the relationship between DCN levels and clinical parameters. The study population consisted of two groups: control group consisted of 13 women with uncomplicated singleton pregnancies in the third trimester. Study group consisted of 14 singleton pregnancies complicated by idiopathic FGR who were admitted to the hospital for delivery in the third trimester of pregnancy. Maternal and fetal DCN levels were measured. Color Doppler flow assessments were performed. Relationship between DCN levels and clinical parameters was determined. Maternal DCN serum levels were significantly higher in complicated pregnancies by idiopathic FGR (p = 0.01). A statistically significant negative correlation was observed between maternal DCN serum levels and neonatal birth weight (r = -0.0506; p = 0.007). There was a significant correlation between umbilical artery (UA) DCN levels and UA S/D ratio (r = 0.512; p = 0.006) and UA RI (r = 0.405; p = 0.036). The risk of high DCN maternal serum levels (>7986.6 pg/mL) in pregnancy complicated by FGR was 8.25 times higher (RR = 8.25; 95% CI, 1.4-46.8). The results of our study showed that the presence of increased DCN levels in women with FGR could contribute to pathogenesis of the disease.
Keywords: Angiogenesis; decorin; Doppler velocimetry; idiopathic fetal growth restriction